AN ANALYSIS OF STUDENTS' READING PROFICIENCY ON NARRATIVE TEXT OF ENGLISH COMPREHENSION SKILLS AT UPT SMP N 10 MEDAN - Grandy Monalisa Sitorus; Merry Susanty Br Tarigan; Chindy Hanggara Rosa Indah (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2024)
This study aims to analyze students' reading ability in understanding narrative text in English and identify influencing factors in UPT SMP N 10 Medan, especially students in class VII-F. The research method used is Qualitative research using instruments such as Observation, test, Documentation and Likert scale, based Questionnaire from 30 students. The results showed that the students' comprehension level showed their narrative text comprehension ability was generally low, with the majority falling into the poor category of 33.33% and very poor 10%. However, most students showed a positive attitude towards reading based on their responses on the questionnaire such as teacher and parent support, reading habits, vocabulary acquisition and understanding in grammar that influenced their reading ability. The findings suggest that increased motivation and learning environment are important in influencing students' narrative text comprehension skills as well as improved learning strategies by teachers.